Peeking into the unique tradition of picking the sea in Muncar, Banyuwangi Regency - Pratama, Andryan Verly Dwi; Faujiyah, Sifa; Sari, Via Arma (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
Indonesia is a country that has extraordinary natural beauty but also has cultural diversity ranging from tribes, ethnicities, and traditions which factors are influenced by the diverse geographical location of Indonesia which makes each region have its own uniqueness. We take the example of the city of Banyuwangi where Banyuwangi is located at the eastern tip of the island of Java has a lot of traditions and cultures. Because in Banyuwangi there are quite a lot of arts and customs that create a lot of culture. One of the traditions that exist and are quite popular in Banyuwangi is petik laut where this tradition is carried out to express gratitude to God for the abundant sea produce. This tradition is carried out on the 15th of Muharram, this tradition is held very lively by the Muncar community, this attracts tourists to come to Muncar and this can boost the economy of the surrounding community. Muncar itself is located at the southern tip which is one of the sub-districts in Banyuwangi Regency. In this study, the method used by the researcher is literature review, by using this method the aim is to identify and analyze various relevant sources concerning the uniqueness of the sea picking tradition in Muncar.